A different path to individualization of welfare services? Co-production of childcare services in Sweden - Vamstad, Johan (Politica, 2015)
The Swedish welfare state has in recent years undergone extensive reforms that have allowed quasi-markets to be formed in several social service areas. The establishment of these quasi-markets has been said to ensure greater individual freedom as well as competition between service providers that will create greater efficiency and better quality. But are quasi-markets really the only means to reach these goals? This paper studies how co-production can be used to reach the same or similar goals. The possibilities of co-production in the welfare state and its significance for what Marshall called social citizenship will be presented, using results from a research project on co-production. The results will show that co-production, like quasi-markets, has its limitations – especially with regard to marginalized groups in society – but that co-production has the potential to combine individualization of social services with social cohesion, provided that there is a political will to do so.